The city as a panacea: cultural policies and participation in Córdoba (Argentina) - Gutiérrez, Mariana Carla (Universidad de Chile. Instituto de la Comunicación e Imagen, 2021)
This article analyzes cultural policies in the context of global valorization of cities as the ideal scale to decentralize political power and to solve problems of cultural democratization. Relevant antecedents are collected on the possibilities and limits that the local level presents in the fields of government, municipal cultural policies and citizen participation. Then, the results of a recent investigation carried out in Córdoba (Argentina) based on interviews and document analysis are reported. We conclude that the participatory dimension of these policies unfolds on a rhetorical level and assigns a more active and purposeful role to their beneficiaries. At the same time, these cultural policies are legitimized since they are conceived as another possible area for the participation of citizens in public affairs, even if the decisions taken are not substantial or participation is unevenly distributed.